Handbook of strategies and strategic processing - Dinsmore, Daniel L.; Fryer, Luke K.; Parkinson, Meghan M. (New York, NY : Routledge, 2020)
"Handbook of Strategies and Strategic Processing provides a state-of-the-art synthesis of conceptual, measurement, and analytical issues regarding learning strategies and strategic processing. Contributions by educational psychology experts present the clearest yet definition of this essential and quickly evolving component of numerous theoretical frameworks that operate across academic domains. This volume addresses the most current research and theory on the nature of strategies and performance, mechanisms for unearthing individuals' strategic behaviors, and both long-established and emerging techniques for data analysis and interpretation"--
Introduction: What are strategies? / Daniel L. Dinsmore, Luke K. Fryer, and Meghan M. Parkinson -- Strategic processing within and across domains of learning / Denis Dumas -- Level of strategies and strategic processing / Daniel L. Dinsmore and Courtney Hattan -- A lifespan developmental perspective on strategic processing / Amélie Rogiers, Emmelien Merchie, Fien De Smedt, Liesje De Backer, and Hilde Van Keer -- Negotiating meaning and engagement : socially shared strategic processing / Deborah L. Butler and Leyton Schnellert -- Commentary: A conceptual framework for defining strategies and strategic processing / Peggy Van Meter and Jacqueline Campbell -- Reading comprehension strategy instruction / Peter Afflerbach, Matthew Hurt, and Byeong-Young Cho -- Six questions regarding strategy use when learning from multiple texts / Alexandra List -- Writing strategies interventions / Steve Graham, Gerardo Bañales, Silza Ahumada, Karen R. Harris, Pamela Muñoz, and Prisila Alvarez -- Mathematics strategy interventions / Kristie Newton -- Science strategy interventions / Doug Lombardi and Janelle M. Bailey -- Strategic processing in history and historical strategy instruction / Susan De La Paz and Jeff Nokes -- Interplay of strategic processes, executive functions, and autonomy support in students with individual differences / Ana Taboada Barber, Kelly B. Cartwright, and Susa Lutz Klauda -- Sharing the load : a strategy to improve self-regulated learning / Martine Baars, Lisette Wijnia, Anique de Bruin, and Fred Paas -- Commentary: An analysis of learning strategies in action / Philip H. Winne -- Surveys and retrospective self-reports to measure strategies and strategic processing / Jan D. Vermunt -- Concurrent and task-specific self-reports / Ivar Bråten, Joseph P. Magliano, and Ladislao Salmerón -- Exploring the utilization of the big data revolution as a methodology for exploring learning strategy in educational environments / Kimberly A. Lawless and Jeremy Riel -- Measuring processing strategies : perspectives for eye tracking and fMRI in multimethod designs / Leen Catrysse, David Gijbels, and Vincent Donche -- Commentary: Measuring strategic processing in concert : reflections and future directions / David Gijbels and Sofie Loyens -- Variable-centered approaches / Rebekah Freed, Jeffrey A. Greene, and Robert D. Plumley -- Person-centered approaches to explaining students' cognitive processing strategies / Luke Fryer and Alex Shum -- Qualitative approaches to the verbal protocol analysis of strategic processing / Byeong-Young Cho, Lindsay Woodward, and Peter Afflerbach -- Commentary: Analyzing strategic processing : pros and cons of different methods / Jennifer G. Cromley -- The future of strategy theory, research, and implementation : roads less traveled / Patricia A. Alexander.
Includes bibliographical references and index.
Daniel L. Dinsmore, Ph. D. is an Associate Professor of Educational Psychology and Research Director for the Northeast Florida Center for STEM Education at the University of North Florida, USA. Luke K. Fryer, Ph. D. is an Associate Professor in the Centre for the Enhancement of Teaching and Learning at The University of Hong Kong, Hong Kong. Meghan M. Parkinson, Ph. D. is the Director of Assessment and Research in the College of Education and Human Services at the University of North Florida, USA.
Description based on online resource; title from digital title page (viewed on April 22, 2020).
eBooks on EBSCOhost
Keywords: Learning strategies; Cognitive learning theory; Educational psychology -- Research; Stratégies d'apprentissage.; Théorie cognitive de l'apprentissage.; Psychopédagogie -- Recherche; EDUCATION -- General; EDUCATION -- Educational Psychology; EDUCATION -- Research; Cognitive learning theory; Educational psychology -- Research; Learning strategies; Handbook; handbooks; Handbooks and manuals; Handbooks and manuals; Guides et manuels